(untitled) (Minerva, 2025)
Our analysis seeks to offer a perspective on what lies at the center of so-called artificial intelligence: the notion of intelligence itself. We seek to address this topic from an angle where philology and philosophy converge, examining the classical meaning of the word “intelligence” through the works of Plato, Aristotle, and Plotinus. This approach allows us to reflect on the meaning of “intelligence” within a significant part of our philosophical tradition. It focuses on the aspects that are inseparable from this concept and its semantic field. Following this examination, we can clarify in what sense artificial intelligence is “intelligence”, or whether this nomenclature functions instead as a metaphor reflecting the historical, sociological, and cultural interellations at work at a given moment.